2019
DOI: 10.3389/fnagi.2019.00244
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Alternative Proteinases in APP Metabolism and Alzheimer’s Disease Pathogenesis: A Focus on MT1-MMP and MT5-MMP

Abstract: Processing of amyloid beta precursor protein (APP) into amyloid-beta peptide (Aβ) by β-secretase and γ-secretase complex is at the heart of the pathogenesis of Alzheimer’s disease (AD). Targeting this proteolytic pathway effectively reduces/prevents pathology and cognitive decline in preclinical experimental models of the disease, but therapeutic strategies based on secretase activity modifying drugs have so far failed in clinical trials. Although this may raise some doubts on the relevance of β- and γ-secreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 221 publications
(304 reference statements)
0
54
0
Order By: Relevance
“…Aβ peptides derive from the proteolytic processing of the amyloid precursor protein (APP) by proteases called βand γ-secretase [4][5][6]. In addition to the generation and deposition of wellcharacterized Aβ40 and Aβ42 amino acid length variants, recent studies also showed the occurrence of several Nand C-terminally truncated or elongated Aβ species that result from alterations in the cleavage by βand γ-secretase or alternative processing by other proteases [7][8][9][10][11][12][13]. Additional heterogeneity in Aβ peptides comes from a number of post-translational modifications that are also found in characteristic Aβ deposits in parenchymal extracellular plaques and cerebral amyloid angiopathy (CAA) [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Aβ peptides derive from the proteolytic processing of the amyloid precursor protein (APP) by proteases called βand γ-secretase [4][5][6]. In addition to the generation and deposition of wellcharacterized Aβ40 and Aβ42 amino acid length variants, recent studies also showed the occurrence of several Nand C-terminally truncated or elongated Aβ species that result from alterations in the cleavage by βand γ-secretase or alternative processing by other proteases [7][8][9][10][11][12][13]. Additional heterogeneity in Aβ peptides comes from a number of post-translational modifications that are also found in characteristic Aβ deposits in parenchymal extracellular plaques and cerebral amyloid angiopathy (CAA) [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although we cannot exclude that other recently discovered APP-processing enzymes (e.g., meprin β, δ-secretase [1,39,2] might cooperate with MT5-MMP, this is rather unlikely because HEK cells do not constitutively express meprin β, and even when overexpressed, this metalloproteinase does not release sAPP95 [40,41]. Moreover, TIMPs do not inhibit meprins [42], while TIMP-2 efficiently blocked the generation of sAPP95 by MT5-MMP.…”
Section: The Generation Of Sapp95 By Mt5-mmp Does Not Involve Other Smentioning
confidence: 85%
“…The accumulation of C99 and C83 after deletion of the IC domain of MT1-MMP was the inverse of the effect caused by the deletion of the IC domain of MT5-MMP, strongly suggesting specific effects of the two homologue proteinases. Although they share 55.6% sequence identity, in the short IC domain of 20 amino acids the homology falls to only 20% [2], which might explain their specificities of action. In this context, only the active MT1-MMP, not the inactive one, is pro-amyloidogenic, and may even behave in some cases as a β-secretase-like [24].…”
Section: The C-terminal Domains Of Mt5-mmp and Mt1-mmp Hold Functionamentioning
confidence: 99%
See 2 more Smart Citations